Macrofaunal diversity on the surface sediment of mangrove habitat adjacent to the seagrass beds at Punangsari River estuary (Malaysian Borneo), South China Sea - Abdulla-Al-Asif; Hamli, Hadi; Idris, Mohd Hanafi; Gerusu, Geoffery James; Ismail, Johan; Abualreesh, Muyassar H.; Mustafa Kamal, Abu Hena (UMT Press, 2023)
Macrofaunal diversity and composition are essential to understanding the ecosystem structures and functions of mangroves in any dynamic estuarine coast. To understand the temporal distribution of macrofaunal community structures and diversity on the surface sediment in the intertidal mangrove forest next to the seagrass beds, this study was conducted at Punang-Sari-River estuary, Lawas, Sarawak (Malaysian Borneo), South China Sea. Sampling was done during post-monsoon, intermediate-September, premonsoon, and monsoon from July 2019 to February 2020. The mean macrofauna abundance was higher pre-monsoon, while Gastropoda Optediceros breviculum (L. Pfeiffer, 1855) was the most abundant (RA = 0.704). Important Species Index (ISI = 70.36) and percentage of contribution (64.97%) were also higher for this species than any other records from the site. The ANOSIM (Analysis of Similarity), Jaccard index and SIMPER (Similarity Percentage Analysis) analysis suggested that the highest species abundance similarity was observed between pre-monsoon and monsoon, while the highest dissimilarity was observed between intermediate-September and pre-monsoon (74.67%). Seasonal PCA, nMDS, and cluster analysis revealed that pre-monsoon and monsoon were comparable in species and individual abundance. The dominance (0.85) was found significantly higher (P < 0.0001) in intermediate-September, while Simpson (0.734), Shannon (1.56) and Evenness indices (0.528) were found higher in monsoon, followed by the higher Margalef richness indices (3.21) in post-monsoon. It was observed that the seasonal ecological parameters were found to be significantly (P < 0.05) different, including the temperature, salinity, rainfall, pore water nitrogenous compounds (NO2 , NO3 and NH3 -N), phosphorus compound (PO4 ) and micro minerals. The Canonical Correspondence Analysis (CCA) results suggested that ecological factors influenced several species. Considering the few studies on mangrove macrofauna in Malaysian Borneo, further research on their trophic structures and food web interactions is very important to disclose their overall characteristics and ecosystem functions.